Second harmonic atomic force microscopy imaging of live and fixed mammalian cells - Dulebo, Alexander; Preiner, Johannes; Kienberger, Ferry; Kada, Gerald; Rankl, Christian; Chtcheglova, Lilia; Lamprecht, Constanze; Kaftan, David; Hinterdorfer, Peter (Ultramicroscopy, 2009)
Higher harmonic contributions in the movement of an oscillating atomic force microscopy (AFM) cantilever are generated by nonlinear tip-sample interactions, yielding additional information on structure and physical properties such as sample stiffness. Higher harmonic amplitudes are strongly enhanced in liquid compared to the operation in air, and were previously reported to result in better structural resolution in highly organized lattices of proteins in bacterial S-layers and viral capsids [J. Preiner, J. Tang, V. Pastushenko, P. Hinterdorfer, Phys. Rev. Lett. 99 (2007) 046102]. We compared first and second harmonics AFM imaging of live and fixed human lung epithelial cells, and microvascular endothelial cells from mouse myocardium (MyEnd). Phase-distance cycles revealed that the second harmonic phase is 8 times more sensitive than the first harmonic phase with respect to variations in the distance between cantilever and sample surface. Frequency spectra were acquired at different positions on living and fixed cells with second harmonic amplitude values correlating with the sample stiffness. We conclude that variations in sample stiffness and corresponding changes in the cantilever-sample distance, latter effect caused by the finite feedback response, result in second harmonic images with improved contrast and information that is not attainable in the fundamental frequency of an oscillating cantilever.
Keywords: eukaryotické buňky; mikroskopie atomárních sil; Animals; Lung; Eukaryotic Cells; Elasticity; pružnost; lidé; Mice; Epithelial Cells; Endothelial Cells; myši; endoteliální buňky; plíce; Microscopy, Atomic Force; zvířata; Myocardium; myokard; epitelové buňky; Humans